The impact of implementing the 2016 WHO Recommendations on Antenatal Care for a Positive Pregnancy Experience on perinatal deaths: an interrupted time-series analysis in Mpumalanga province, South Africa - Yogan Pillay; Tina Lavin; Robert Clive Pattinson; Erin Kelty; David Brian Preen (BMJ Global Health)
Objectives To investigate if the implementation of the 2016 WHO Recommendations for a Positive Pregnancy Experience reduced perinatal mortality in a South African province. The recommendations were implemented which included increasing the number of contacts and also the content of the contacts.Methods Retrospective interrupted time-series analysis was conducted for all women accessing a minimum of one antenatal care contact from April 2014 to September 2019 in Mpumalanga province, South Africa. Retrospective interrupted time-series analysis of province level perinatal mortality and birth data comparing the pre-implementation period (April 2014–March 2017) and post-implementation period (April 2018–September 2019). The main outcome measure was unadjusted prevalence ratio (PR) for perinatal deaths before and after implementation; interrupted time-series analyses for trends in perinatal mortality before and after implementation; stillbirth risk by gestational age; primary cause of deaths (and maternal condition) before and after implementation.Results Overall, there was a 5.8% absolute decrease in stillbirths after implementation of the recommendations, however this was not statistically significant (PR 0.95, 95% CI 0.90% to 1.05%; p=0.073). Fresh stillbirths decreased by 16.6% (PR 0.86, 95% CI 0.77% to 0.95%; p=0.003) while macerated stillbirths (p=0.899) and early neonatal deaths remained unchanged (p=0.499). When stratified by weight fresh stillbirths >2500 g decreased by 17.2% (PR 0.81, 95% CI 0.70% to 0.94%; p=0.007) and early neonatal deaths decreased by 12.8% (PR 0.88, 95% CI 0.77% to 0.99%; p=0.041). The interrupted time-series analysis confirmed a trend for decreasing stillbirths at 0.09/1000 births per month (−0.09, 95% CI −1.18 to 0.01; p=0.059), early neonatal deaths (−0.09, 95% CI −0.14 to 0.04; p=<0.001) and perinatal mortality (−1.18, 95% CI −0.27 to −0.09; p<0.001) in the post-implementation period. A decrease in stillbirths, early neonatal deaths or perinatal mortality was not observed in the pre-implementation period. During the period when additional antenatal care contacts were implemented (34–38 weeks), there was a decrease in stillbirths of 18.4% (risk ratio (RR) 0.82, 95% CI 0.73% to 0.91%, p=0.0003). In hypertensive disorders of pregnancy, the risk of stillbirth decreased in the post-period by 15.1% (RR 0.85; 95% CI 0.76% to 0.94%; p=0.002).Conclusion The implementation of the 2016 WHO Recommendations for a Positive Pregnancy Experience may be an effective public health strategy to reduce stillbirths in South African provinces.